Correction: Identifying the electrocatalytic active sites of a Ru-based catalyst with high Faraday efficiency in CO2-saturated media for an aqueous Zn–CO2 system. Issue 30 (3rd July 2020) - Kim, Jeongwon; Yang, Yejin; Seong, Arim; Noh, Hyuk-Jun; Kim, Changmin; Joo, Sangwook; Cho, Ara; Zhang, Linjuan; Zhou, Jing; Wang, Jian-Qiang; Han, Jeong Woo; Mahmood, Javeed; et al.
Abstract : Correction for 'Identifying the electrocatalytic active sites of a Ru-based catalyst with high Faraday efficiency in CO2 -saturated media for an aqueous Zn–CO2 system' by Jeongwon Kim et al., J. Mater. Chem. A, 2020, DOI: ; 10.1039/d0ta03050c .